Implementasi Ayat Qaulan Ma’rufan dalam Pembiasaan Akhlaq dan Adab di Kuttab Al Husnayain Surakarta - Pamungkas, Maulana Al Bana; Fauzi, Sriyono (ANWARUL, 2024)
This article discusses the application of the Qur'anic verse qaulan ma'rufan in the habituation of good manners and adab every day when speaking in accordance with the Qur'an and sunnah. The aim is to observe the learning process in its application. This research uses descriptive qualitative methods with data collection techniques through observation, interviews and documentation. The implementation of qaulan ma'rufan verse in the habituation of good manners and adab in Kuttab Al Husnayain Surakarta is able to be one of the solutions in fortifying children from despicable manners, especially when speaking. This is also one of the resident programs of the vision and mission of Kuttab Al Husanayain Surakarta which expects the emergence of a qur'ani generation with qur'ani morals, with the provision of the Qur'an and sunnah as well as religious knowledge and the arrangement of the heart and akhlaq guided in piety.